Carbon stock potential on various land covers in heath forest in Liang Anggang, South Kalimantan - Muhammad Abdul Qirom; Tri Ani Windawati; Kissinger Kissinger; Abdi Fithria (Jurnal GALAM, 2021)
ABSTRACTHeath forest serves as a large carbon and water storage. This study aims to obtain information on carbon storage potential of each carbon component in heat forest in Liang Anggang Protection Forest. Data collection was carried out on six types of land cover, namely: agricultural land, barren land/settlement, scrub, peat soil, and forest. The carbon components were measured such as trees, undergrowth, litter, necromass, and soil. Measurement plots were established with size of 40 x 100 m for trees and necromasses > 30 cm in size, and sub-plots measuring 5 x 40 m for trees with a diameter of 5–30 cm as many as 5 plots for each type of land cover. The understorey and litter components used a plot with size of 0.5 x 0.5 m. In tree pools, carbon stock was determined by indirect measured with alometric model, while the other was used by direct measurenment. The results showed that carbon in the soil contributed the largest potential carbon storage (> 95%) of the total carbon storage in all land cover types. The pattern of the proportion of carbon storage in this forest type was similar to the peat swamp forest type. On heat forest, carbon stock potential on scrub was 318.8 Mg/Ha and the potential of heat forest type was the lowest (256.8 Mg/Ha ). In total, the average carbon storage potential was 285.01 ± 48.78 Mg/Ha. The carbon storage at this location reached 2.99 x 105 tons of carbon, or equivalent to carbon absorption of 1,10 X 106 CO2 e ton CO2e. The large amount of carbon storage in heath forest in the study area has the potential to support diversification and optimization of land use through a carbon trading scheme.Key words: trade, agriculture, proportion, scheme, soil